Penguatan Ekonomi Kreatif Berbasis Potensi Lokal melalui Pendampingan sebagai Upaya Menumbuhkan Jiwa Entrepreneur pada Mahasiswa Prodi Ekonomi - Rohmah, Miftakhur; Priyono, Sigit; Rahmadani, Rafika; Rifa'i, Muhamad Nanang; Liana Sari, Nuri (Jurnal Indonesia Mengabdi, 2022)
Indonesia is currently transforming from a developing country into a developed country, with one of the conditions being that 14% of the total population is an entrepreneur. Higher education is a forum that is expected to be able to contribute to increasing the number of entrepreneurs in Indonesia. However, this will be difficult to realize if graduates from tertiary institutions have the mindset that they are only ready to find work but are not ready to create jobs. From these problems, the service team provides a solution, namely by providing Entrepreneurship education or entrepreneurship education to foster an entrepreneurial spirit in students through creative economic activities. So that this community service activity will later be able to change the mindset of students and be able to form students into business actors who have an entrepreneurial spirit in an innovative and creative way in order to develop business capabilities or be able to see opportunities with the spirit of Pro-growth (encouraging economic growth), Pro-job ( creating and expanding employment), and Pro-poor (reducing poverty). The service consists of two stages, stage 1) Providing motivation and introduction to the concept of entrepreneurship and stage 2) Assisting creative economic activities based Local potential.